The Effect of Creative Problem-Solving Model to Enhance Scientific Creativity: Study in Static Fluid Physics Learning - Shinta Dewi; Iwan Permana Suwarna; Ahmad Suryadi (Universitas Lambung Mangkurat, 2024)
The purpose of this study is to ascertain how applying the Creative Problem-Solving model in physics classes affects students' scientific creativity when studying static fluids and how applying the model can improve students' scientific creativity. This study employed a quasi-experimental method, with the population of focus being 11th-grade science students at SMAN 4 South Tangerang, totaling 200 students. The sample in this study involves 78 students selected through the purposive sampling technique and divided into two groups (experimental and control), each comprising 39 students. Both groups were assessed for their skills through pretests and post-tests. The instruments used in this research consisted of 5 structured essay questions referring to three indicators of scientific creativity dimensions developed by Hu and Adey. The result of this study shows that the data generated, based on the Mann-Whitney U test, indicates a significant difference between the post-test scores of the two groups, with a Sig. Value of 0.000, which is below 0.05. The N-gain results also showed a gain of 0.56 in the experimental group and 0.43 in the control group. In conclusion, the Creative Problem-Solving model influenced students' scientific creativity, and it effectively improved students' scientific creativity. The research implications suggest that teachers should implement this teaching method to improve students' scientific creativity skills, enabling them to actively and skillfully address various complex problems in everyday life.